2018
DOI: 10.1002/ajmg.a.38634
|View full text |Cite
|
Sign up to set email alerts
|

ICD‐10 impact on ascertainment and accuracy of oral cleft cases as recorded by the Brazilian national live birth information system

Abstract: We compared Brazilian oral cleft (OC) frequencies between the population-based Brazilian System of Live Birth (SINASC) and the hospital-based Latin American Collaborative Study of Congenital Malformations (ECLAMC), trying to understand the paucity of cleft of lip and palate (CLP) in the first system. SINASC uses the International Classification of Disease version 10 (ICD-10) for congenital defects coding, ECLAMC uses ICD-8 with modifications. In SINASC, the CLP frequency was 1.7 per 10,000 (95% confidence limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…SINASC includes information on place of delivery (hospital or home), the mother who gave birth (including name, age, place of residence, marital status, education, number of children, and number of previous live and still births), the pregnancy (number of prenatal appointments, length of gestation, type of pregnancy: singleton or twin, type of delivery); and the newborn (gestational age, birth weight, sex, ethnicity, the presence and type of birth anomalies for live and stillbirths, and 1- and 5-min APGAR score for live births) (da Saúde, 2011). SINASC uses the International Classification of Disease Version 10 (ICD-10) for coding congenital defects (do Nascimento et al, 2018).…”
Section: Databases Used In Health Outcomes/policy Research In Brazilmentioning
confidence: 99%
See 1 more Smart Citation
“…SINASC includes information on place of delivery (hospital or home), the mother who gave birth (including name, age, place of residence, marital status, education, number of children, and number of previous live and still births), the pregnancy (number of prenatal appointments, length of gestation, type of pregnancy: singleton or twin, type of delivery); and the newborn (gestational age, birth weight, sex, ethnicity, the presence and type of birth anomalies for live and stillbirths, and 1- and 5-min APGAR score for live births) (da Saúde, 2011). SINASC uses the International Classification of Disease Version 10 (ICD-10) for coding congenital defects (do Nascimento et al, 2018).…”
Section: Databases Used In Health Outcomes/policy Research In Brazilmentioning
confidence: 99%
“…In addition, under-registration of births is still common in some regions of the country and inconsistency of records in variables, such as mother’s education, race, and number of prior childbirths, is still high in North and Northeast regions (Oliveira et al, 2015; Hunter and Sugiyama, 2018). SINASC, in combination with SIM (the Mortality Information System) and SIH (the Hospital Information System), has been used to study the impacts, burden, and/patterns of diseases (Paixao et al, 2018), pregnancy-related hospitalizations (Moura et al, 2018), impact of socio-economic inequalities on prenatal consultation (Mallmann et al, 2018), factors affecting neonatal mortality (Kropiwiec et al, 2017; Paixao et al, 2018), the use of ICD-10 coding system on congenital disease ascertainment (do Nascimento et al, 2018). SINASC and SIM/SIH also provide data that are used as parameters in the HTA studies.…”
Section: Databases Used In Health Outcomes/policy Research In Brazilmentioning
confidence: 99%
“…Several ReLAMC registries presented prevalence rates for cleft lip (Q36) and cleft lip and palate (Q37) that suggested under registration or coding problems. Oral cleft information such as the proportion of each type of cleft could be used when establishing data quality indicators for congenital anomaly registries (Groisman et al, 2019), and indicated several coding problems in the live birth part of the Brazilian registry (Nascimento, Castilla, Dutra, & Orioli, 2018). The ICD-10 classification of oral clefts could induce oral cleft coding errors in those registries that use the ICD-10 classification without any extension such as the BPA (Nascimento et al, 2018).…”
Section: Health Indicatorsmentioning
confidence: 99%
“…Oral cleft information such as the proportion of each type of cleft could be used when establishing data quality indicators for congenital anomaly registries (Groisman et al, 2019), and indicated several coding problems in the live birth part of the Brazilian registry (Nascimento, Castilla, Dutra, & Orioli, 2018). The ICD-10 classification of oral clefts could induce oral cleft coding errors in those registries that use the ICD-10 classification without any extension such as the BPA (Nascimento et al, 2018). The ICD-10 BPA codes Q36.90 and Q36.99 allow the separation of unilateral cleft lip from a unspecified cleft lip, and the Q37.99 code allows the registration of an unspecified cleft lip with cleft palate case.…”
Section: Health Indicatorsmentioning
confidence: 99%
“…Disease coding is a common practical data structuralization method that is critical in many fields such as disease surveillance [3], health services management [4], and clinical research [5]. The coding quality can still be improved, and computer-aided coding systems have been considered to increase the accuracy [6,7]. Numerous models have been implemented in recent years [8-11], but they were considered inapplicable [2].…”
Section: Introductionmentioning
confidence: 99%